Comparison between all-suture and biocomposite anchors in the arthroscopic treatment of traumatic anterior shoulder instability: A retrospective cohort study - Pantekidis, Ioannis (J Orthop, 2021)
PURPOSE: Suture anchors have revolutionized arthroscopic surgery, enabling direct soft tissue-to-bone repair. There are many types of anchors still used in arthroscopic shoulder operations. We sought to compare the clinical outcome of all-suture and biocomposite anchors when used in arthroscopic Bankart repair for patients suffering from anterior shoulder instability. METHODS: A single-center retrospective cohort study of 30 patients (mean age: 26.6 years, SD: 8.8 years, male/female ratio: 5/1, mean follow up: 28 months, SD: 23.8, range: 12–92) with anterior shoulder instability was conducted. Patients were divided into 2 groups based upon the type of suture anchors used for the Bankart repair: group A (14 patients) used only all-suture anchors and group B (16 patients) used only biocomposite anchors. Outcomes reported were postoperative dislocations, positive shoulder apprehension test, self-reported sense of shoulder instability, return to activities of daily living, return to sports, patient satisfaction and complications. Patient reported outcome measures (PROMs) used were the Rowe Score for Instability, Constant Shoulder Score, Walch Duplay Score, The American Shoulder and Elbow Surgeons (ASES) Shoulder Score, Oxford Shoulder Instability Score and external rotation at 90° of arm abduction, external rotation at 0° of arm abduction, forward flexion, abduction, adduction and internal rotation. RESULTS: Rates of postoperative shoulder dislocation demonstrated no significant difference between the 2 groups (p > .05). Four postoperative dislocations happened, two in each group (14.3% and 12.5% for all suture only and biocomposite only groups, respectively), with three of them being traumatic. In addition, no significant differences were observed amongst groups regarding shoulder apprehension test (group A: 85.7% vs. group B: 93.8%), sense of shoulder instability (7.1% vs. 6.3%), return to activities of daily living (group A: 85.7% vs. group B: 93.8%), return to sports (group A: 85.7% vs. group B: 87.5%), patient satisfaction (moderate level: group A 21.4% vs. group B 12.5%), and PROMs. CONCLUSION: The short-term failure rate and clinical/functional outcomes of arthroscopic Bankart repair using all-suture anchors is similar to the use of biocompatible anchors. LEVEL OF EVIDENCE: Level III, retrospective cohort study.